Pengaruh Inflasi dan Ekspor Terhadap Pertumbuhan Ekonomi di Indonesia Tahun 1988-2023 - Andini, Putri; Salsabilla, Syifa Aisya; Syahafidan, Feisya Arfani; Salsabila, Ervia Syifa; Shanti, Elena Rista Kurnia; Hakim, Aqilla Fadya Hayya (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
This research aims to analyze the influence of inflation and exports on Indonesia's economic growth within the periodization of 1988-2023. A quantitative method was applied through multiple linear regression analysis to explore the relationship between independent variables (inflation and exports) and the dependent variable (economic growth). Secondary data sources were obtained from the World Bank. Empirical tests revealed that inflation shows a significant negative contribution to economic growth, while exports did not display statistically meaningful influence. With a determination coefficient of 55.3%, this research model indicates that inflation and export variables are capable of explaining most of the variability in the context of economic growth, with several residual factors potentially influenced by external variables in the international market. This study provides substantive implications for economic policy, with emphasis on mechanisms for controlling the national economic dynamics of Indonesia.